2015
DOI: 10.5194/os-11-965-2015
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the mantle and crustal helium isotope signature in the Mediterranean Sea using a high-resolution regional circulation model

Abstract: Abstract. Helium isotopes ( 3 He, 4 He) are useful tracers for investigating the deep ocean circulation and for evaluating ocean general circulation models, because helium is a stable and conservative nuclide that does not take part in any chemical or biological process. Helium in the ocean originates from three different sources, namely, (i) gas dissolution in equilibrium with atmospheric helium, (ii) helium-3 addition by radioactive decay of tritium (called tritiugenic helium), and (iii) injection of terrige… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This model correctly simulates the main structures of the thermohaline circulation of the Mediterranean Sea, with mechanisms having a realistic timescale compared to observations (Ayache et al, 2015a). In particular, tritium (Ayache et al, 2015a) and helium isotope simulations (Ayache et al, 2015b) have shown that the EMT signal from the Aegean sub-basin is realistically simulated during early 1995. However, some aspects of the model still need to be improved: for instance the too-weak formation of Adriatic Deep Water (AdDW), followed by a low contribution to the EMDW in the Ionian sub-basin.…”
Section: Circulation Modelmentioning
confidence: 78%
See 2 more Smart Citations
“…This model correctly simulates the main structures of the thermohaline circulation of the Mediterranean Sea, with mechanisms having a realistic timescale compared to observations (Ayache et al, 2015a). In particular, tritium (Ayache et al, 2015a) and helium isotope simulations (Ayache et al, 2015b) have shown that the EMT signal from the Aegean sub-basin is realistically simulated during early 1995. However, some aspects of the model still need to be improved: for instance the too-weak formation of Adriatic Deep Water (AdDW), followed by a low contribution to the EMDW in the Ionian sub-basin.…”
Section: Circulation Modelmentioning
confidence: 78%
“…A time-step of 20 minutes is applied. The same approach was used to simulate the εNd (neodymium) distribution in the Mediterranean Sea (Ayache et al, 2016), and the mantle and crustal helium isotope signature (Ayache et al, 2015b), as well as to model the anthropogenic tritium invasion (Ayache et al, 2015a), and CFC and anthropogenic carbon storage (Palmiéri et al, 2015).…”
Section: The Tracer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacan and Jeandel, 2005;Jeandel, 1993;Jeandel et al, 1998;Frank, 2002;Goldstein and Hemming, 2003;Piotrowski et al, 2004Piotrowski et al, , 2012Stichel et al, 2012;Martin et al, 2012;Pena et al, 2013;Molina-Kescher et al, 2014;Arsouze et al, 2008). However, because Nd is particle reactive, Nd parameters are also successfully used to study Nd exchange between dissolved and particulate phases (Bertram and Elderfield, 1993;Henry et al, 1994;Jeandel et al, 1995;Tachikawa et al, 1999Tachikawa et al, , 2003Garcia-Solsona et al, 2014;Rousseau et al, 2015;Haley et al, 2014).…”
mentioning
confidence: 99%